EVALUATION OF DYNAMICS OF DIFFERENT METHODS OF TREATMENT FOR RESPIRATORY ALLERGOSIS - F. Kh. Irsalieva; K. F. Nizamov (American Journals Publishing, 2024)
The dynamics of different treatment methods with different treatment methods was assessed in 120 patients with pollen sensitization. The indicators of the quality of life of patients improved with the use of both specific and non-specific methods of treatment (p <0.05). The best results were obtained with the use of allergen-specific immunotherapy, autoserotherapy (p <0.001).
Keywords: Respiratory allergies, hay fever, quality of life, therapy methods